CÓMO ESCRIBIR EL INFORME FINAL DE UNA TESIS - Tito Huamaní, Pedro L. (2008)
The final report of the thesis research is becoming a headache for most graduates of masters and doctoral degrees, due to be presented in an organized and systematic investigated the issue, describing step by step the task done. In the case of administrative sciences, one of the major constraints for the submission of these documents is the lack of role models or guides, so that this text provides some guidelines to help graduates of master’s and doctoral degrees in the development of the final investigation report.